Learning Strategy Model through Santri Seating Management at Anwaha - Mahmud; Syahrani (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Seating is often treated as a logistical matter, but in pesantren learning it intersects with traditional instructional practices, teacher supervision, peer interaction, and the social organization of learning. This study explored how ustadz (teachers) and santri (students) at Pesantren Anwaha experienced and interpreted seating management and how these interpretations informed learning-strategy selection. A qualitative phenomenological design was used, with data collected through observation, in-depth interviews, and documentation and analyzed through significant statements, thematic categorization, textural and structural description, and synthesis of experiential meaning. Five contextual seating patterns were identified: classical, halaqah or circular, group, paired, and rotational seating. Classical arrangements supported direct explanation and monitoring; halaqah and group arrangements supported dialogue, musyawarah, and collaborative discussion; paired seating facilitated memorization, reading, correction, and peer support; and rotation was used to distribute positional experience and participation opportunities. Across participants’ accounts, seating became pedagogically meaningful when aligned with learning objectives, material characteristics, santri conditions, and intended interaction patterns. The resulting model positions seating management as a contextual component of instructional decision-making in pesantren. The findings describe site-specific experiential relationships rather than causal effects.